Hygroscopic inertia of a room: evaluation of finishing materials contribution - Nuno M. M. Ramos (2005)
The practical application of the hygroscopic inertia concept in building design demands for a simple prediction strategy of the impact of interior renderings and furnishings. Significant aspects of the evaluation of finishing materials contribution to the hygroscopic inertia are presented in this paper.